Pengaruh Profil Yayasan terhadap Citra Sekolah di SDIT Tiara Aksara - Fadilah, Ahmad Arif; Jovansky, Aisyah Amelia (TSAQOFAH, 2022)
This study aims to determine the profile of SDIT Tiara Aksara Tangerang City as one of the superior schools, this study was conducted to know more deeply how the profile of a superior school is. This research is a quantitative research which analyzed by survey and descriptive method. Data were collected through field observations, interviews and documents related to the Tiara Aksara foundation in the form of organizational reports and personal documents as well as visual documents such as photos. Based on research on the effect of the profile of the foundation on the image of the school at SDIT Tiara Aksara Tangerang in this thesis it was concluded that there was a positive and significant influence between the profile of the foundation on the image of the SDIT Tiara Aksara Tangerang school. This can be seen from the calculation of the SPSS researchers with the obtained t-count = 7.747 and t-table = 2.048, then t-count = 7.747 > t-table 2.048 at a significant level of 5%. The profile of the foundation's contribution to the school's image made by the calculation results of the SPPS correlation is 0.826 with a coefficient of determination of 0.682 which means that 68.2% of the school's image is determined by the profile of the foundation, while 31.8% is determined by other factors not analyzed in this study.